1996
DOI: 10.1016/s0014-5793(96)01149-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of the terminal repeat GAGC trimer, the major Rep78 binding site, in adeno‐associated virus DNA replication

Abstract: The adeno-associated virus (AAV) terminal repeats (TR) are cis required, and the AAV encoded Rep78 protein is trans required, for AAV DNA replication. The Rep78 protein recognizes and interacts with at least three regions within the TR DNA. The major binding site, with the highest affinity for Rep78 binding, is within the TR stem (nt 36-16) and includes the 'core' GAGC trimer (GAGC 3, nt 33-22; Fig. 2) sequence. In this study mutations were made within the GAGC trimer and these mutants assayed for their abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Previously, we found that E1 aa353–649 was able to provide some helper function, in boosting basal autonomous wt AAV2 DNA replication in differentiating keratinocytes [36]. However, wt AAV2 biology studies and rAAV production are almost always carried out in HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we found that E1 aa353–649 was able to provide some helper function, in boosting basal autonomous wt AAV2 DNA replication in differentiating keratinocytes [36]. However, wt AAV2 biology studies and rAAV production are almost always carried out in HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Five days after transfection, low-molecular-weight Hirt DNA was isolated [1, 6], agarose gel-electrophoresed, subjected to Southern blotting as described previously [36-38], and then probed with 32 P-eGFP DNA. No Dpn I digestion is needed at this late time of harvest as all transfected input plasmid DNA has been degraded by day 3.…”
Section: Methodsmentioning
confidence: 99%
“…The AAV terminal repeat (TR) substrate was generated by the ligation of three separate synthetic oligonucleotides as described previously (43). The TR was 5Ј end-labeled with polynucleotide kinase using […”
Section: Methodsmentioning
confidence: 99%
“…Mutational analysis has identified a core 22-bp sequence required for stable Rep binding to linear TR substrates (27). This RBE includes the tetrameric GAGC repeat identified by several groups as necessary for stable Rep binding to both linear and hairpinned TR substrates (4,8,19,20,32,36). Moreover, chemical interference assays indicate that all major Rep contacts within the linear portion of the hairpinned TR fall within the RBE (1,25,27).…”
mentioning
confidence: 99%
“…Although the contribution of the RBE to Rep-catalyzed trs nicking has not been determined, mutant AAV genomes containing multiple transversions in the RBE replicate at much lower levels than do wild-type (wt) genomes (4). This observation has led to the conclusion that stable Rep binding to the AAV TR is necessary for efficient origin nicking and subse-quent viral replication.…”
mentioning
confidence: 99%